Pengaruh kemampuan awal, nilai karakter dan keceerdasan emosionalterhadap prestasi belajar pendidikan pembentukan brigadir polisi siswa SPN Selopamioro di Kecamatan Imogiri Kabupaten Bantul tahun anggaran 2013 - Khuriyah Lina Suryani (Universitas Sarjanawiyata Tamansiswa, 2015)
The Effect of Initial Ability, Character and Emotional Intelligence Values toward the Learning Achievement of Police Brigadier Education among Students of Selopamioro State Police School in Imogiri, Bantul in the 2013 Fiscal Year. Thesis: Graduate School of Education, Sarjanawiyata Tamansiswa Wiyata Yogyakarta, 2014. This study aims to determine the effect of initial ability, character and emotional intelligence values toward the learning achievement of police brigadier education among students of SPN Selopamioro, Imogiri, Bantul. This study belongs to a correlative quantitative approach involving all 240 students of SPN Selopamioro as the population. Out of these, 148 students were chosen as the sample based on Krajcik and Morgan table. The findings indicate that there is a simultaneous and partial significant positive influence of initial ability, character and emotional intelligent values to the dependent variable of the learning achievement of students SPN formation Police Brigadier Selopamioro.